Toxic Myocardial Injury in a Patient With Coronary Atherosclerosis, Caused by Acute Poisoning With Gaseous Chlorine - K. G. Alidzhanova; A. Yu. Moiseyeva; A. M. Pashayeva; M. M. Potskhveriya; G. A. Gazaryan; S. Yu. Kambarov (Неотложная медицинская помощь, 2021)
Acute chlorine gas poisoning leads to activation of the sympathetic nervous system and, as a consequence, dysfunction of the cardiovascular system (CVS). We report a clinical case of toxic myocardial injury with gaseous  chlorine. In a man with coronary artery disease and polypathy, toxic  myocardial injury mimicked acute coronary syndrome (ACS) and was accompanied by a large area of left ventricular microvascular dysfunction, which did not coincide with the areas of blood supply of altered coronary arteries; the dynamics of electrocardiographic changes resembled  myocardial stunning in Takotsubo syndrome (TS). The effect of chlorine on CVS, features of clinical and instrumental diagnostics and differentiation of primary / secondary CT and ACS are discussed.